Phytochemical analysis of 7 types of potatoes - Imuda, Rahman (2018)
Phytochemical can be found at different levels in plants that famous for the uses in healing chronic disease. In this study, seven types of sweet potatoes variety which is Japanese Sweet Potato (JP), Jewel Sweet Potato (JeP), Hannah Sweet Potato (HP), Australian Sweet Potato (AP), Garret Sweet Potato (GP) Purple Sweet Potato (PP), and Vitato Sweet Potato (VP) were tested in quantitative analysis. The study will focus on the quantitative analysis to measure the quantity of these phytochemical that present in the samples by using a standard procedure. The data obtained revealed the presence of medicinally important bioactive compounds such as tannin, flavonoid, terpenoid, and phenolic compound. The comparison analysis between seven samples determined which sample has highest phytochemical content. The presence of these medicinally active secondary metabolites justifies the use of the sweet potatoes as herbal treatment of various diseases. The phytochemical analysis of various types of potatoes is important to find out the potential phytochemical that exist in this plant. The high potential phytochemical can be used for medical purpose and commercialized. The result for this study shown Australian Sweet Potato has the highest value of tannin (2.12 µgram/ml), followed by Jewel Sweet Potato without skin (1.82 µgram/ml) and Jewel Sweet Potato (1.68 µgram/ml). For the flavonoid, the Purple Sweet potato shown the highest value (391.61 µgram/ml) followed by Japanese Sweet Potato with skin (377.07 µgram/ml) and Japanese Sweet Potato without skin (293.28 µgram/ml). For the terpenoid. Vitato Sweet potato has the highest value (97.39 µgram/ml) followed by Purple Potato without skin (96.16 µgram/ml) and Vitato Sweet Potato with skin (91.35 µgram/ml). Hannah Sweet Potato without skin has the highest contain of phenol compound (1285.23 µgram/ml) followed by Jewel Sweet Potato with skin (1274.46 µgram/ml) and Purple Sweet Potato with skin (1038.35 µgram/ml).